2015
DOI: 10.1111/1911-3846.12179
|View full text |Cite
|
Sign up to set email alerts
|

The Earnings Quality Information Content of Dividend Policies and Audit Pricing

Abstract: Recent studies indicate dividends are associated with higher‐quality earnings. Our study extends the literature by examining whether dividends' information is associated with auditors' assessment of their clients' earnings quality. Our results show that auditors charge lower fees to dividend‐paying clients than to nondividend‐paying clients and the average fee discount ranges from 6.0 to 10.6 percent. More importantly, we find dividends have an interactive effect with respect to earnings persistence and earnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 52 publications
1
16
0
2
Order By: Relevance
“…They report that this effect is more pronounced in countries with weak investor protection and high opacity. Lawson and Wang () examine the information content of dividends through audit pricing and find that dividend‐paying firms pay lower audit fees than nonpayers. The authors explain that dividends provide information to auditors, reducing the concerns over the earnings quality of clients.…”
Section: Introductionmentioning
confidence: 99%
“…They report that this effect is more pronounced in countries with weak investor protection and high opacity. Lawson and Wang () examine the information content of dividends through audit pricing and find that dividend‐paying firms pay lower audit fees than nonpayers. The authors explain that dividends provide information to auditors, reducing the concerns over the earnings quality of clients.…”
Section: Introductionmentioning
confidence: 99%
“…By examining Lilian et al (2012), the dividend has a signal of high obedience on accounting standard, because of the high involvement of shareholders in monitoring and checking the strategic decision. He et al (2017) found that the relationship between dividend and actual return has a positive effect; it strengthens Lawson and Wang (2016) by stressing on this policy as a guideline for nonmanipulation activity. Considering the advantages of dividend to level up the positive investor's perception maximally, so this research uses this policy as a moderation variable.…”
Section: Second: the Earnings Value-based Hypothesismentioning
confidence: 86%
“…A qualidade do lucro responde por importante parcela das pesquisas em contabilidade, podendo ser caracterizada como a capacidade de se sustentar no futuro, i. e., o lucro atual com alta (baixa) correlação com lucros futuros teriam alta (baixa) qualidade (Lustosa, Fernandes, Nunes, & De Araujo Junior, 2010 (Caskey & Hanlon, 2013;Dichev et al, 2013;Lawson & Wang, 2016), auditoria (Lambert, Jones, Brazel, & Showalter, 2017;Lennox, Wu, & Zhang, 2016), custo de capital (Affleck-Graves, Callahan, & Chipalkatti, 2002;Ghosh & Moon, 2010;Karamanou & Nishiotis, 2009;Lambert, Leuz, & Verrecchia, 2007;Liu, Ning, & Davidson III, 2010;Munteanu, 2011;Persakis & Iatridis, 2017), estrutura de governança corporativa (Athanasakou & Olsson, 2012;Choi, Lee, & Park, 2013;Core & Guay, 1999;El-Sayed Ebaid, 2013;Fan & Wong, 2002;Hazarika, Karpoff, & Nahata, 2012;Houqe & Zijl, 2010;Jiang & Anandarajan, 2009;Jiang, Lee, & Anandarajan, 2008;Kent, Kent, Routledge, & Stewart, 2016;Lin & Hwang, 2010;Machuga & Teitel, 2009;Sáenz González & García-Meca, 2014;Shiri, Vaghfi, Soltani, & Esmaeli, 2012;Shleifer & Vishny, 1997), adoção às International Financial Reporting Standards (IFRS) (Barth, 2013;Black & Nakao, 2017;Daske, Hail, Leuz, & Verdi, 2008;Healy & Palepu, 2001;…”
Section: Qualidade Do Lucrounclassified